The Sunset of "Quality Control" in Modern Trademark Licensing - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2007)
Historically, based on the premise that trademark protection is about consumer welfare, trademark law has allowed trademark licensing only as long as licensors control the quality of the products bearing the licensed marks. Ever since its adoption, however, this rule has been difficult to enforce because it hinges on a concept that is ambiguous and difficult to frame in a legal context: quality control. Unsurprisingly, the consequence has been inconsistent case law and much uncertainty as to what represents valid licensing. In addition, in the past decades, courts have proven increasingly reticent to strictly apply this rule and have declared agreements with minimal or no control valid as long as the public was not misled. The rise of recent practices such as, inter alia, promotional trademark licensing has contributed to this trend and highlighted the growing unsustainability of the current requirement in today's economy. This Article argues against this uncertainty and advocates for an amendment to the current rule that would allow licensing with or without control. In support of this change, this Article offers evidence that, contrary to the original intention of the law, this rule is negatively affecting competition in the marketplace and allowing unfair competitors to initiate frivolous legal actions. This Article therefore proposes that, rather than focusing on an increasingly sterile and confusing requirement - quality control - the courts should assess the validity of licensing by focusing directly on the result of the agreements - whether the use of the licensed marks will deceive consumers.